Influence of Job Satisfaction on Doctors’ Level of Organizational Commitment in Hospitals - Huma Akram, Yaamina Salman, Sana Akram, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To investigate the influence of job satisfaction level on organizational commitment of doctors doing jobs in public and private hospitals located in Pakistan Study Design: This explanatory study was conducted in Hospitals of Karachi and Lahore from January 2019 to January 2020. Place and Duration of study: Data was collected from doctors working in hospitals of Lahore including Fatima Memorial Hospital, De’montmorency College of Dentistry (Punjab Dental Hospital), Faryal Dental College and hospital and Jinnah Hospital. Data was also collected from Karachi including Jinnah Post medical college and hospital and Fauji Foundation Hospital. Materials and Methods: Questionnaires were given to collect data from doctors. 300 questionnaires were circulated but 251 questionnaires were given back and usable. To evaluate the collected data, simple linear regression analysis was done. Results: 35.1% (88) of the doctors surveyed were male & 64.9% (163) were female. The results of research demonstrated that there is direct and positive effect of job satisfaction level on all the three dimensions of organizational commitment (affective, continuance and normative commitment) and complete score of organizational commitment. Conclusion: The findings of research gave important knowledge to management of hospitals and managers dealing with Human resources (HR) employed in hospitals about how to make them contented, devoted, and faithful to hospitals.